School Effectiveness in Adventist Junior High Schools in North Sulawesi Province - Mozes M Wullur; Henny N Tambingon; Viktory N J Rotty; Marshela Pondaag (International Journal of Social Service and Research (IJSSR), 2023)
This study aims to analyze and describe the influence of the principal's managerial abilities, teacher performance, school culture and parental involvement on school effectiveness. This research is classified as a quantitative study where the data collected is in the form of numerical data from the results of the distribution of questionnaires, four free variables, namely the managerial ability of the principal (X1), teacher performance (X2), School Culture (X3) and parental involvement (X4) for bound variables, namely school effectiveness (Y). This study used 101 teacher respondents at Adventist Junior High School in North Sulawesi Province and a total of 202 populations were randomly sampled so that each respondent had an equal chance of being sampled. The data were then analyzed using multiple regression analysis to answer five research hypotheses. The results showed that the results that these four variables together have a positive and significant effect on school effectiveness.